Bosques nativos, servicios ecosistémicos culturales y cambio climático - Minaverry, Clara M (Universidad Nacional del Litoral, 2021)
The purpose is to analyze regulation and public policies about cultural ecosystem services, native forests, biodiversity and climate change in Argentina and Chile.